Revitalisasi Peran Mubaligh Dan Mubalighah Dalam Dakwah Inklusif Di Perkotaan: Studi Penguatan Kapasitas di YKBS Depok - Aspriansyah; Supriadi; Surato; Tukijo; Sobirin (LPPI UMN AL WASHLIYAH, 2025)
This study aims to analyze the role of male and female preachers (mubaligh and mubalighah) in the context of inclusive Islamic preaching (dakwah) within urban areas, focusing on a case study at the Kreasi Bangun Semesta Foundation (YKBS) in Limo, Depok City. The research employs a descriptive qualitative approach using in-depth interviews, participatory observation, and document analysis. Findings indicate that preachers in the YKBS environment face complex challenges, particularly with social diversity, the lack of contextual dakwah training, and limited utilization of digital media. Preaching activities remain largely normative and lack contextual adaptation to the urban setting. Therefore, revitalizing the role of preachers requires capacity strengthening in social communication, multicultural understanding, and community-based preaching strategies. This study recommends an inclusive, integrative, and participatory dakwah model as a strategic solution to address the dynamic challenges of urban Islamic preaching.